Master bag low-oxygen packaging system: Quality evolution of ground beef patties during storage, blooming and display presentation. (September 2015) - Uboldi, Eleonora; Zanoletti, Miriam; Franzetti, Laura; Limbo, Sara
Highlights: Low O2 master packages increased beef patties' distribution life up to 10 days. Beef patties stored in master bag for 8–10 days bloomed within 2 h after opening. The stretch film perforation did not affect the blooming kinetics. Display life evolution comparable with those of patties never stored in master bag. Abstract: Case-ready ground beef patties have been packed using a low-oxygen master bag packaging system with oxygen scavengers consisting in: storage for 10 days in low oxygen master bag (0.5 °C), blooming for different times and display life in air for 2 days (5 °C). The kinetics of blooming was studied as well as the effect of a PVC stretch film (with an O2 TR – oxygen transmission rate – equal to 20, 000 cm 3  m −2 24 h −1 (23 °C, 0% RH, 1 bar of pO2 ) with or without perforation on myoglobin oxygenation and color changes. During storage in master bags, the scavengers allowed the progressive conversion of surface oxymyoglobin into deoxymyoglobin through the reversible formation of metmyoglobin (transient discoloration). The microflora shifted from aerobic to anaerobic with a predominance of lactic acid bacteria. The concentration of Brochotrix thermosphacta remained constant over the entire storage period. The removal of the trays from the master bag and the subsequent storage in air allowed the blooming of the meat within 60 min. The high O2 TR value of the stretched PVC guaranteed rapid oxygen exchange, whereas the presence of the perforation did not contribute to a further increase in the superficial oxygenation. The quality decay during the display life was comparable to that of samples never stored in master bags. In conclusion, the use of low oxygen master bags was able to prolong the storage time on ground beef patties ensuring the current shelf life achieved with traditional packaging system.